Analisis Praktik Jual Beli Produk Pertanian Bayar Panen dalam Perspektif Hukum Ekonomi Islam di Desa Barurejo Kecamatan Siliragung Kabupaten Banyuwangi - Lely Ana Ferawati Ekaningsih; Aula Izatul Aini; Imroatul Mutiah (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
This study aims to determine the practice of implementing the sale and purchase of agricultural products to pay harvest/respite in Barurejo Village, Siliragung District, Banyuwangi Regency. To find out about the legal views of Islamic economics on the implementation of buying and selling pay harvest. The type of research used in this study is a case study that is single-case design. Data analysis using interactive model analysis techniques. The results of the study, namely the practice of buying and selling are in accordance with the terms and also the pillars of sale and purchase, and buying and selling of this harvest does not contain elements of persecution, because both parties benefit from each other. In the practice of buying and selling agricultural products, the harvest in Barurejo Village, Siliragung Subdistrict, Banyuwangi Regency is in accordance with the objectives of Islamic economic law, namely a sense of empathy among people to create mutual benefit where the price increase the seller gets the price in lieu of the length of payment and the buyer gets the desired item without issuing money in cash, adding a relatively small amount of price and not burdening one party